Wood preservatives - Mohamed Nasir, Syaidatul Hazira (2009)
Wood was treated using wood preservatives to prolong it useful life. Wood that was preserved is more durable than wood that was not preserved with wood preservatives. There are three types of preservatives; water borne preservatives, oil type preservatives and organic solvent preservatives. However, wood preservatives can cause hazard when not used properly.